On Complements and Relative Complements in Distributive Soft Rough Lattice - P. Geetha; C. Shyamala Devi (International Journal of Mathematics And its Applications, 2017)
Soft sets and rough sets are both mathematical tools for dealing with problems that contain uncertainty. Soft rough set is a connection between these two mathematical approaches to vagueness and it is the generalization of rough set with respect to the soft approximation space. Nagarajan et al. [9] defined the direct product of soft lattices. The complements of soft lattice has been given by Nagarajan et al. [10]. The complements of rough set has been defined by Ameri et al. [1]. In this paper, we first define complements of soft rough set and also define the complements and relative complements of soft rough lattice. We discuss some theorems related to the complements and relative complements of distributive soft rough lattice with an example.